An Accuracy Analysis of Translation in English-Indonesian Bilingual Children’s Storybooks through Back-Translation - Yeni Erlita; Berlin Sibarani; Juli Rachmadani Hasibuan; Johannes Jefria Gultom (Universitas Negeri Gorontalo, 2026)
This study evaluates the translation accuracy of the English-Indonesian bilingual children’s storybook Purple and Walter: Save the Trees using the Back-Translation method to ensure its reliability for bilingual education. Employing a qualitative descriptive design with textual analysis, the research analyzed 65 linguistic units comprising sentences and dialogue segments following the four-step